Vessel diameter and related hydraulic traits of 31 Eucalyptus species arrayed along a gradient of water availability - Sebastian Pfautsch; Craig Macfarlane; Marco Harbusch; Anita Wesolowski; Renee Smith; Matthias Boer; Mark G. Tjoelker; Peter B. Reich; Mark A. Adams (Ecology, 2016)
We present two comprehensive data sets that describe xylem vessel diameters and related sapwood traits for species of Eucalyptus from arid and semi‐arid woodlands and forests in Australia. Between 2009 and 2014, sapwood of mature trees was sampled in south‐western, south‐eastern and eastern Australia. One additional species was sampled from tropical north‐western Australia. The first data set describes samples collected from the basal stem section (130 cm above ground) of three individuals of 31 species of which eight species were replicated at sites that differed in climatic conditions. The second data set describes vessel characteristics of three trees from each of 10 species that were sampled at 8 m below the tree apex. The sampled trees of these 10 species are also part of the first data set. In total, we report diameters (D) for over 25 100 vessels, from 494 digital images taken from 117 trees. We also report vessel frequencies, void‐to‐wood ratios, sapwood densities and hydraulically weighted vessel diameters (Dh). Supporting data of the first data set include tree diameter at breast height (130 cm above ground), tree height, sample locations, and summary climate data. In this data set, diameter of individual vessels ranges from 10 to over 300 μm, and vessel frequency from 360 to 9070 vessels cm −2 . Wood density ranges from 0.47 to 0.96 g cm −3 . Void‐to‐wood ratio ranges from 6% to 27% and Dh ranges from 46 to 236 μm. Mean annual rainfall (P) at sample sites ranges from 246 to 2274 mm and FAO 56 reference evaporation (E) from 777 to 2110 mm. The aridity index (E/P) ranges from 0.15 to 2.93 (dimensionless). Tree diameters range from 9 to 90 cm and tree heights range from 6 to 70 m. D and Dh in the second data set range from 11 to 271 and 68 to 205 μm, respectively. These datasets will make a valuable contribution to future continental‐scale and global‐scale studies of the relationship between xylem hydraulic architecture and climate. The data sets are unique in the sense that they are phylogenetically constrained, allowing in‐depth assessment of plasticity of hydraulic attributes within a single tree genus.